2008
DOI: 10.1158/1078-0432.ccr-07-1802
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic-Genetic Interactions in theAPC/WNT, RAS/RAF, andP53Pathways in Colorectal Carcinoma

Abstract: Purpose: Early events in colorectal tumorigenesis include mutation of the adenomatous polyposis coli (APC) gene and epigenetic hypermethylation with transcriptional silencing of the O 6 -methylguanine DNA methyltransferase (MGMT), human mut L homologue 1 (hMLH1), and P16/CDKN2A genes. Epigenetic alterations affect genetic events: Loss of MGMT via hypermethylation reportedly predisposes to guanine-to-adenine or cytosine-to-thymine (G:C!A:T) transition mutations in KRAS and P53, and silencing of hMLH1 leads to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 58 publications
(66 reference statements)
3
59
1
Order By: Relevance
“…16 Our reported frequency of K-ras overexpression and mutations (48.9% and 41.1%, respectively), together with the significant correlation with reduced OS, was comparable to that reported in some previous studies. In this context, Bazan et al, 16 Suehiro et al, 46 and Pajkos et al 47 reported a significant correlation between K-ras codon 12 mutations and aggressive forms of disease with reduced survival rates. In contrast, Akkiprik et al 7 and Bouzourene et al 15 demonstrated that the presence or absence of K-ras mutations was not correlated with prognosis in patients with stage II CRC.…”
Section: Discussionmentioning
confidence: 98%
“…16 Our reported frequency of K-ras overexpression and mutations (48.9% and 41.1%, respectively), together with the significant correlation with reduced OS, was comparable to that reported in some previous studies. In this context, Bazan et al, 16 Suehiro et al, 46 and Pajkos et al 47 reported a significant correlation between K-ras codon 12 mutations and aggressive forms of disease with reduced survival rates. In contrast, Akkiprik et al 7 and Bouzourene et al 15 demonstrated that the presence or absence of K-ras mutations was not correlated with prognosis in patients with stage II CRC.…”
Section: Discussionmentioning
confidence: 98%
“…BRAF acts as direct effector of RAS and through the activation of MEK, promotes tumourogenesis (Sclafani et al, 2013). The BRAF pV600E (c.1799T > A) mutation occurs in 15-20% of CRCs and has important genetic, prognostic, and therapeutic implications (Koinuma et al, 2004;Suehiro et al, 2008). A recent literature review and meta-analysis indicates the incidence of BRAF mutation in sporadic MLH1 MSI CRC to be 63.50% (95% CI: 46.98% -78.53%) (Parsons et al, 2012) Likewise most CRCs containing activated BRAF mutation have CIMP, whereas CIMP and the BRAF mutation are uncommon in Lynch syndrome-associated cancers (≤1%) (Lagerstedt Robinson et al, 2007).…”
Section: Sporadic Colorectal Cancer With Msimentioning
confidence: 99%
“…14 MGMT methylation or loss of MGMT protein expression is reportedly associated with an increased frequency of mutations in the KRAS oncogene and P53 tumour-suppressor gene in colorectal cancer, particularly G4A transitions, consistent with a causative function of G4A mutagenesis in tumourigenesis. 11,12,[15][16][17][18] However, other studies have found no specific associations with this sequence change, 19,20 or only a weak association with the presence of a G4A mutation within one of the four cancer-associated genes KRAS, P53, APC and b-catenin. 21 Association studies between MGMT methylation, CIMP and microsatellite stability (MSS) status in colorectal cancer have also reported inconsistent findings.…”
mentioning
confidence: 99%
“…21 Association studies between MGMT methylation, CIMP and microsatellite stability (MSS) status in colorectal cancer have also reported inconsistent findings. MGMT methylation has been correlated with MSS and low-level MSI, 17,20 though the existence of low-level MSI as an entity distinct from MSS remains controversial. Although MGMT methylation was initially included as one of the panel of markers to predict CIMP in some studies, [22][23][24][25] it has since been shown to be a poor marker for this epigenetic phenotype and may be independent of CIMP status altogether.…”
mentioning
confidence: 99%